Greater knee varus angle and pelvic internal rotation after landing are predictive factors of a non-contact lateral ankle sprain. (July 2021) - Mineta, Shinshiro; Inami, Takayuki; Hoshiba, Takuma; Higashihara, Ayako; Kumai, Tsukasa; Torii, Suguru; Hirose, Norikazu
Abstract: Objectives: This study aimed to clarify the kinematic, kinetic characteristics associated with lateral ankle sprain. Design: A 16-month prospective cohort study. Setting: Laboratory. Participants: A total of 179 college athletes. Main outcome measures: Joint kinematics, moment during single-leg landing tasks, and ankle laxity were measured. The attendance of each participating team, injury mechanism, existence of body contact, presence of orthosis, with or without medical diagnosis, and periods of absence were recorded. Results: Twenty-nine participants incurred lateral ankle sprain during non-contact motion. The Cox regression analysis revealed that greater knee varus peak angle (hazard ratio: 1.16 [95% confidence interval: 1.10–1.22], p  < 0.001) and greater pelvic internal rotation peak angle toward the support leg were associated with lateral ankle sprain (hazard ratio: 1.08 [95% confidence interval: 1.02–1.15], p  = 0.009). The cut-off values for each predictive factor were −0.17° (area under the curve = 0.89, p  < 0.001) and 6.63° (area under the curve = 0.74, p < 0.001), respectively. Conclusions: A greater knee varus peak angle and pelvic internal rotation peak angle after single-leg landing are predictive factors for lateral ankle sprain. Highlights: We evaluated single-leg landing and ankle laxity in 179 athletes. 29 athletes sustained a lateral ankle sprain within 16 months. Greater knee varus & pelvic internal rotation peak angle were predictive factors. The time to peak pelvic internal rotation in injured group was significantly early. There was no significant difference in knee varus time to peak between the groups.